2002
DOI: 10.1046/j.1365-2141.2002.03820.x
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of human haematopoiesis in non‐obese diabetic/severe combined immunodeficient mice by clonal cells expanded from single CD34+CD38 cells expressing Flk2/Flt3

Abstract: Summary. In the present study, we examined the expression of Flk2/Flt3, a tyrosine kinase receptor, on human cord blood CD34+ haematopoietic progenitor/stem cells. + cells in the culture with Flk2/Flt3 ligand, stem cell factor, thrombopoietin, and a complex of interleukin 6/soluble interleukin 6 receptor were individually transplanted into NOD/SCID mice. At 20 to 21 weeks after the transplantation, three out of 10 clones harvested at d 7 of culture, and three out of six clones at d 14 could reconstitute human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 49 publications
3
28
0
Order By: Relevance
“…In the NOD/SCID/IL2r␥ null newborn system, the hCD34 ϩ hCD38 Ϫ hCD90 ϩ population was highly enriched for HSCs capable of long-term reconstitution as compared with the hCD34 ϩ hCD38 Ϫ hCD90 Ϫ CB fraction (F. Ishikawa, unpublished data). The vast majority of hCD34 ϩ hCD38 Ϫ cells expressed hFlt3 at a low level as previously reported (38). Furthermore, the hCD34 ϩ hCD38 Ϫ hCD90 ϩ CB population expressed hFlt3.…”
Section: % Of the Hcd34supporting
confidence: 87%
“…In the NOD/SCID/IL2r␥ null newborn system, the hCD34 ϩ hCD38 Ϫ hCD90 ϩ population was highly enriched for HSCs capable of long-term reconstitution as compared with the hCD34 ϩ hCD38 Ϫ hCD90 Ϫ CB fraction (F. Ishikawa, unpublished data). The vast majority of hCD34 ϩ hCD38 Ϫ cells expressed hFlt3 at a low level as previously reported (38). Furthermore, the hCD34 ϩ hCD38 Ϫ hCD90 ϩ CB population expressed hFlt3.…”
Section: % Of the Hcd34supporting
confidence: 87%
“…However, it remains possible that FLT3 might be expressed and important already in the HSC compartment in man. There is in fact strong evidence in support of human candidate HSCs expressing FLT3, [28][29][30] in contrast to mouse HSCs that are predominantly FLT3 Ϫ . 16,20 …”
Section: Discussionmentioning
confidence: 99%
“…27 Resolving the conflicting results with regard to a potential role of FLT3 receptor and ligand in regulation of mouse HSCs has considerable implications for normal and leukemic hematopoiesis in man. Several studies have suggested that FLT3 is expressed on candidate normal human HSCs, [28][29][30] and greater than 30% of acute myeloid leukemias (AMLs) have activating mutations in the FLT3 receptor. 31,32 Thus, it is important to establish the normal cellular targets of FLT3 mutations, because, if these include HSCs, it might affect not only the biology but also the therapeutic targeting and resistance of FLT3-mutated leukemic clones.…”
Section: Introductionmentioning
confidence: 99%
“…[39][40][41][42] In the mouse, the HSC population has been shown to consist entirely of the Flt-3 Ϫ cells. [43][44][45][46][47] However, recent studies by Sitnicka et al 48 and Ebihara et al 49 have shown that virtually all human BM and umbilical cord blood lymphomyeloid stem cells capable of reconstituting nonobese diabetic/severe combined immunodeficiency (NOD-SCID) mice expressed the flt-3 gene. Moreover, the Flt-3 ligand, FL, efficiently supports the viability of human HSCs 48 but has no such effect on HSCs from the mouse.…”
Section: Discussionmentioning
confidence: 99%